Trust management system in wireless sensor networks: Design considerations and research challenges - Ishmanov, F. (Wiley Blackwell, 2015)
Trust is an important factor in wireless sensor networks (WSNs) in terms of security enhancement and successful collaboration. Trust management (TM) can ensure that all communicating nodes are trustworthy during authentication, authorisation, or key management, which makes traditional security services more robust and reliable. Moreover, by helping to find reliable nodes, TM improves cooperation among nodes, which is vital for improvement of system performance. Trust estimations and management are highly challenging issues because of the unique features and susceptibility of WSNs to different attacks. These factors prevent direct application of schemes suited to other networks and require careful design in a TM system. Hence, our objective is to discuss and present the concept and design factors of TM in WSNs in detail. Moreover, we explore the current state of research as well as open research issues by reviewing proposed trust computation and management schemes in WSNs. Â© 2014 John Wiley & Sons, Ltd.